2010
DOI: 10.1093/cercor/bhq234
|View full text |Cite
|
Sign up to set email alerts
|

Altered Firing Rates and Patterns in Interneurons in Experimental Cortical Dysplasia

Abstract: Cortical dysplasia (CD) is associated with severe epilepsy in humans, and the in utero irradiation of fetal rats provides a model of this disorder. These animals show a selective loss of inhibitory interneurons, and the surviving interneurons have a reduced excitatory synaptic drive. The current study was undertaken to see how alterations in synaptic input would affect spontaneous firing of interneurons in dysplastic cortex. We recorded spontaneous action potentials and excitatory and inhibitory postsynaptic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 73 publications
3
32
0
Order By: Relevance
“…The functional roles of SST interneurons in epilepsy and other neurological diseases are complex and less well-established than for PV interneurons. Reduction in excitability in both SST interneurons and PV interneurons is observed in a rat model of cortical dysplasia (46). Mice lacking the transcription factor Dlx1 display subtype-specific reduction of excitability in cortical SST interneurons and calretinin-expressing interneurons, but not in PV interneurons, and these mice showed generalized electrographic seizures (47).…”
Section: Sodium Currents In Cell Bodies Of Cortical Gabaergic-inhibitorymentioning
confidence: 99%
“…The functional roles of SST interneurons in epilepsy and other neurological diseases are complex and less well-established than for PV interneurons. Reduction in excitability in both SST interneurons and PV interneurons is observed in a rat model of cortical dysplasia (46). Mice lacking the transcription factor Dlx1 display subtype-specific reduction of excitability in cortical SST interneurons and calretinin-expressing interneurons, but not in PV interneurons, and these mice showed generalized electrographic seizures (47).…”
Section: Sodium Currents In Cell Bodies Of Cortical Gabaergic-inhibitorymentioning
confidence: 99%
“…However, changes in membrane excitability of neurons have consistently been described in neuronal migration disorders (Castro et al, 2001;Trotter et al, 2006;George and Jacobs, 2011;Zhou and Roper, 2011) and could contribute to abnormal network excitability. Therefore, we first obtained somatic whole-cell current-clamp recordings from granule cells of wild-type controls (n ϭ 14) and age-matched LIS1 mutants (n ϭ 14) to compare passive membrane and intrinsic firing properties.…”
Section: Intrinsic Excitability Of Mature Granule Cellsmentioning
confidence: 99%
“…In support of this conclusion, a recent examination of interneuron firing rates in a model of cortical dysplasia reported that reductions in glutamatergic drive of interneurons were correlated with reduced spontaneous firing rates of these cells (Zhou and Roper 2010).…”
Section: Discussionmentioning
confidence: 85%